Composite carbon fiber as well as preparation method and application thereof

By covering the zirconia layer and the polyimide layer on the carbon fiber, the problem of easy falling off the interface of the nozzle composite material is solved, and the material's temperature resistance and ablation resistance and interface performance are significantly improved.

CN119593199AInactive Publication Date: 2025-03-11CHANGZHOU ZHONGKE FEIHANG COMPOSITE MATERIALS TECH CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411901944.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional coating coating methods are prone to easy interface fall off in nozzle composite materials, resulting in insufficient ablation resistance performance of the material in high temperature and high pressure environments.

Method used

The carbon fiber is coated by combining the zirconia layer and the polyimide layer, and the temperature and ablation resistance of the material is improved through the zirconia layer, and the interfacial shear resistance of the material is enhanced through the polyimide layer.

Benefits of technology

The mechanical properties and temperature resistance and ablation resistance of composite carbon fiber materials have been significantly improved, and the interfacial performance and comprehensive performance of the material have been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593199A_ABST
    Figure CN119593199A_ABST
Patent Text Reader

Abstract

The invention relates to a composite carbon fiber as well as a preparation method and application thereof. The composite carbon fiber comprises a carbon fiber, a zirconium oxide layer coated on the surface of the carbon fiber and a polyimide layer coated on the surface of the zirconium oxide layer. In the composite carbon fiber material, the zirconium oxide layer can improve the temperature resistance and ablation resistance, the polyimide layer can enhance the interface shear resistance, and the zirconium oxide layer and the polyimide layer cooperate with each other, so that the prepared composite carbon fiber material is excellent in mechanical property and temperature resistance and ablation resistance. According to the preparation method disclosed by the invention, a carbon fiber-zirconium oxide-polyimide multilayer interface from inorganic to organic is prepared, modulus and temperature resistance gradient from the carbon fiber to polyimide resin is constructed, and the interface performance of the composite carbon fiber material is improved. The zirconium oxide can partially enter the polyimide layer, so that the interface fusion between the zirconium oxide and the polyimide is improved, and the comprehensive performance of the composite carbon fiber material is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon fiber, and in particular to a carbon fiber and a preparation method and application thereof, and in particular to a composite carbon fiber and a preparation method and application thereof. Background Art

[0002] With the rapid development of the aerospace industry, research on near-Earth solid rockets has gradually deepened. The nozzle is the outlet of high-temperature and high-pressure gas in the combustion chamber and is an important component for energy conversion. It ensures the normal combustion of propellant and enables the engine to obtain thrust. The nozzle is in extreme service conditions when the solid rocket is running, with a temperature exceeding 1200℃, a pressure greater than 6MPa and a surface gas velocity greater than 100m / s.

[0003] The development of composite materials for nozzle diffusion section is the focus of solid rocket research. The development of a new generation of high-performance equipment has higher requirements for the ablation resistance and interface performance of composite materials. Therefore, in recent years, scientists have focused on the research of high-temperature resistant and ablation-resistant composite materials. CN115286407A discloses a Cf / Ta4HfC5-SiC high-temperature resistant composite material and its preparation method. The invention shortens the preparation cycle, increases the density of the material, and the prepared composite material has good ablation resistance; CN115028472A discloses a method for preparing an anti-oxidation and ablation coating on the surface of a C / C composite material. The invention overcomes the problem of different coating thickness in traditional processes and further improves the anti-oxidation and ablation resistance of the surface coating of the C / C composite material; CN114163252A discloses a method for preparing a high-temperature silicon carbide ceramic-based composite material. The invention improves the anti-oxidation and ablation resistance of silicon carbide ceramic-based composite materials and is expected to be applied in the aerospace field. It can be seen that ceramic coatings can improve the high-temperature and ablation resistance of composite materials. In addition, the development of ablation-resistant composite materials plays a vital role in the development of the aerospace industry.

[0004] However, the traditional coating method often has the problem of easy interface shedding in actual application, which is due to the combustion of internal high-temperature propellant on the one hand and the erosion of external high-speed airflow on the other hand. Therefore, how to enhance the interface strength of composite materials while ensuring the high-temperature and ablation resistance of composite materials is the focus of research by technicians in this field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a composite carbon fiber and its preparation method and application. In the composite carbon fiber material of the present invention, the zirconium oxide layer can improve its heat resistance and ablation resistance, and the polyimide layer can enhance its interface shear resistance. The two cooperate with each other to prepare the composite carbon fiber material with excellent mechanical properties and heat resistance and ablation resistance. The present invention prepares a multilayer interface of carbon fiber-zirconium oxide-polyimide from inorganic to organic, constructs a modulus and temperature resistance gradient from carbon fiber to polyimide resin, and improves the interface performance of the composite carbon fiber material. Zirconium oxide will partially enter the polyimide layer, improve the interface fusion between zirconium oxide and polyimide, and help improve the comprehensive performance of the composite carbon fiber material.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite carbon fiber, comprising a carbon fiber, a zirconium oxide layer coated on a surface of the carbon fiber, and a polyimide layer coated on a surface of the zirconium oxide layer.

[0008] In the composite carbon fiber material of the present invention, the zirconium oxide layer can improve its heat resistance and ablation resistance, and the polyimide layer can enhance its interface shear resistance. The two cooperate with each other to prepare the composite carbon fiber material with excellent mechanical properties and heat resistance and ablation resistance. The present invention prepares a multilayer interface of carbon fiber-zirconium oxide-polyimide from inorganic to organic, constructs a modulus and heat resistance gradient from carbon fiber to polyimide resin, and improves the interface performance of the composite carbon fiber material. Zirconium oxide will partially enter the polyimide layer, improve the interface fusion between zirconium oxide and polyimide, and help improve the comprehensive performance of the composite carbon fiber material.

[0009] Preferably, the carbon fiber includes any one of T300 carbon fiber, T700 carbon fiber, T800 carbon fiber or T1000 carbon fiber, or a combination of at least two of them. Typical but non-limiting combinations include a combination of T300 carbon fiber and T700 carbon fiber, or a combination of T700 carbon fiber, T800 carbon fiber and T1000 carbon fiber.

[0010] Preferably, the thickness of the zirconium oxide layer is 0.1 μm-2 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm or 2 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] Preferably, the thickness of the polyimide layer is 0.2 μm-5 μm, for example, 0.2 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] Preferably, the polyimide comprises a thermosetting polyimide with a cross-linked structure.

[0013] In a second aspect, the present invention provides a method for preparing the composite carbon fiber as described in the first aspect, the preparation method comprising the following steps: first immersing the carbon fiber in a zirconium oxychloride sol, and then performing a gelation reaction to obtain a carbon fiber coated with a zirconium oxide layer; and second immersing the carbon fiber coated with the zirconium oxide layer in a polyamide solution, and then performing an imidization reaction to obtain the composite carbon fiber.

[0014] Preferably, the carbon fibers are pretreated before the first impregnation.

[0015] Preferably, the pretreatment comprises cleaning, degumming and pickling performed in sequence.

[0016] The present invention can remove the sizing agent on the surface of the carbon fiber and perform surface acid etching through pretreatment, further increasing the specific surface area of ​​the carbon fiber, and can also further increase the surface activity of the carbon fiber, facilitating subsequent coating treatment and improving the interface compatibility of the carbon fiber and zirconium oxide.

[0017] Preferably, the cleaning agent comprises ethanol and / or isopropanol.

[0018] Preferably, the degumming method includes a reflow process.

[0019] Preferably, the medium for the reflux treatment comprises acetone.

[0020] Preferably, the solvent of the acid leaching comprises nitric acid.

[0021] Preferably, the mass concentration of the nitric acid is 30%-50%, for example, 30%, 35%, 40%, 45% or 50%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the immersion time of the acid leaching is 4h-12h, for example, it can be 4h, 5h, 6h, 8h, 10h or 12h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the concentration of the zirconium oxychloride sol is 0.01 mol / L-2 mol / L, for example, it can be 0.01 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] The present invention can further control the thickness and uniformity of the zirconium oxide layer by further limiting the concentration of the zirconium oxychloride sol. Within the preferred concentration range of the zirconium oxychloride sol, the thickness of the zirconium oxide layer is moderate and uniform, and the on-demand design of the zirconium oxide coating layer can be achieved.

[0025] Preferably, the insulation temperature of the first impregnation is 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the insulation time of the first impregnation is 1 h-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 2.8 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the reaction temperature of the gelation reaction is 200°C-800°C, for example, 200°C, 300°C, 400°C, 600°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the reaction time of the gelation reaction is 0.5h-24h, for example, 0.5h, 1h, 5h, 10h, 15h, 20h or 24h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the environmental atmosphere of the gelation reaction is a first inert gas atmosphere.

[0030] Preferably, the first inert gas atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.

[0031] The present application can further regulate the crystallinity of the zirconium oxide layer by regulating the reaction temperature and reaction time of the gelation reaction, realize the transformation of the zirconium oxide layer from an amorphous form to a crystalline form, improve the strength of the zirconium oxide layer, and further improve the strength of the composite carbon fiber material. At the preferred reaction temperature and reaction time of the gelation reaction, the zirconium oxide layer has good crystallinity and high strength, and the composite carbon fiber material has high strength.

[0032] Preferably, the monomer of the polyamidoamine solution includes any one or a combination of at least two of 4,4-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene, pyromellitic anhydride or 3,3,4,4-biphenyltetracarboxylic dianhydride, and a typical but non-limiting combination includes a combination of 4,4-diaminodiphenyl ether and 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene, or a combination of 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene, pyromellitic anhydride and 3,3,4,4-biphenyltetracarboxylic dianhydride.

[0033] Preferably, the concentration of the polyamidoamine solution is 0.01 mol / L-1 mol / L, for example, 0.01 mol / L, 0.1 mol / L, 0.5 mol / L, 0.7 mol / L or 1 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] The present invention can further regulate the thickness and uniformity of the polyimide layer by further limiting the concentration of the polyamide solution. Within the preferred concentration range of the polyamide solution, the thickness of the polyimide layer is moderate and uniform, and the on-demand design of the polyimide coating layer can be achieved.

[0035] Preferably, drying is further performed after the second impregnation and before the imidization reaction.

[0036] Preferably, the drying insulation temperature is 20°C-30°C, for example, it can be 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the drying heat preservation time is 1 h-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the reaction temperature of the imidization reaction is 200°C-400°C, for example, 200°C, 250°C, 300°C, 350°C or 400°C, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0039] Preferably, the reaction time of the imidization reaction is 0.5 h-6 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the ambient atmosphere of the imidization reaction is a second inert gas atmosphere.

[0041] Preferably, the second inert gas atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.

[0042] The present invention can further regulate the stability of the polyimide layer by further regulating the reaction temperature and reaction time of the imidization reaction, thereby improving the interface shear resistance of the composite carbon fiber material. At the preferred reaction temperature and reaction time of the imidization reaction, the stability of the polyimide layer is good, and the interface shear resistance of the composite carbon fiber is excellent.

[0043] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0044] (1) Pretreating the carbon fiber to obtain pretreated carbon fiber, the pretreatment comprising sequentially cleaning, degumming and acid immersion, the cleaning agent comprising ethanol and / or isopropanol, the degumming method comprising reflux treatment, the reflux treatment medium comprising acetone, the acid immersion solvent comprising nitric acid, and the acid immersion time being 4h-12h.

[0045] (2) After the carbon fiber is first immersed in the zirconium oxychloride sol, a gelation reaction is performed to obtain a carbon fiber coated with a zirconium oxide layer. The reaction temperature of the gelation reaction is 200° C.-800° C., and the reaction time is 0.5 h-24 h.

[0046] (3) After the zirconium oxide layer-coated carbon fiber is immersed in the polyamide solution for the second time, an imidization reaction is performed to obtain the composite carbon fiber. The reaction temperature of the imidization reaction is 200° C.-400° C., and the reaction time is 0.5 h-6 h.

[0047] In a third aspect, the present invention provides an application of the composite carbon fiber as described in the first aspect, wherein the composite carbon fiber is applied to aerospace structural materials.

[0048] Compared with the prior art, the present invention has at least the following beneficial effects:

[0049] (1) In the composite carbon fiber material of the present invention, the zirconium oxide layer can improve its heat resistance and ablation resistance, and the polyimide layer can enhance its interface shear resistance. The two work together to prepare a composite carbon fiber material with excellent mechanical properties and heat resistance and ablation resistance.

[0050] (2) The present invention prepares a multilayer interface of carbon fiber-zirconia-polyimide from inorganic to organic, constructs a modulus and temperature resistance gradient from carbon fiber to polyimide resin, and improves the interface performance of the composite carbon fiber material.

[0051] (3) In the composite carbon fiber of the present invention, zirconium oxide partially enters the polyimide layer, thereby improving the interface fusion between zirconium oxide and polyimide, and helping to improve the comprehensive performance of the composite carbon fiber material. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 is a schematic diagram of the structure of the composite carbon fiber prepared in Example 1 of the present invention;

[0053] Figure 2 is a scanning electron microscope image of the untreated carbon fiber in Example 1 of the present invention;

[0054] Figure 3is a scanning electron microscope image of the pretreated carbon fiber in Example 1 of the present invention;

[0055] Figure 4 is a scanning electron microscope image of the carbon fiber coated with only a zirconium oxide layer prepared in Example 1 of the present invention;

[0056] Figure 5 is a scanning electron microscope image of the carbon fiber coated with a zirconium oxide layer and a polyimide layer prepared in Example 1 of the present invention;

[0057] Figure 6 is a scanning electron microscope image of the composite carbon fiber prepared in Example 1 of the present invention;

[0058] Figure 7 is a scanning electron microscope image of the composite carbon fiber prepared in Example 1 of the present invention after ablation;

[0059] Figure 8 is a scanning electron microscope image of the composite carbon fiber prepared in Comparative Example 1 of the present invention after ablation;

[0060] Among them, 1 is carbon fiber, 2 is zirconium oxide layer, and 3 is polyimide layer. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0062] The preparation method of zirconium oxychloride sol comprises the following steps: mixing zirconium oxychloride and deionized water in proportion, stirring for 1h-2h until the solution becomes colorless, then adding ammonia water in proportion, stirring for 6h-8h, and standing for 12h-15h after the reaction is completed to obtain a zirconium oxychloride solution of a specific concentration.

[0063] The preparation method of the polyamic acid solution comprises the following steps:

[0064] Method 1: Mix the monomer of polyamic acid and deionized water in proportion, stir for 3h-5h until the solution is uniform and transparent, and obtain a polyamic acid solution of a specific concentration;

[0065] Method 2: Mix the first monomer of polyamic acid and deionized water in proportion, stir for 3h-5h until the solution is uniform and transparent, then add the second monomer in proportion, stir for 6h-8h, and obtain a polyamic acid solution of a specific concentration.

[0066] Example 1

[0067] The present embodiment provides a composite carbon fiber, which includes T300 carbon fiber, a zirconium oxide layer coated on the surface of the T300 carbon fiber, and a polyimide layer coated on the surface of the zirconium oxide layer, wherein the coating thickness of the zirconium oxide is 1 μm, and the coating thickness of the polyimide is 2 μm.

[0068] The preparation method of the composite carbon fiber provided in this embodiment comprises the following steps:

[0069] (1) The T300 carbon fiber is sequentially cleaned with ethanol, subjected to reflux treatment for degumming, and subjected to acid immersion, and then washed with deionized water until the pH of the washing liquid is 7, thereby obtaining a pretreated carbon fiber; the reflux treatment medium comprises acetone; the acid immersion solvent comprises nitric acid with a mass concentration of 40%, and the acid immersion time is 10 hours;

[0070] (2) After the carbon fiber is first impregnated in zirconium oxychloride sol, a gelation reaction is performed to obtain a carbon fiber coated with a zirconium oxide layer; the concentration of the zirconium oxychloride sol is 0.2 mol / L, the insulation temperature of the first impregnation is 60° C., the insulation time is 2 h, the reaction temperature of the gelation reaction is 400° C., the reaction time is 1 h, and the ambient atmosphere is an argon atmosphere;

[0071] (3) After the zirconium oxide layer-coated carbon fiber is immersed in a polyamide solution for a second time, drying and imidization reaction are carried out in sequence to obtain the composite carbon fiber; the polyamide solution is prepared by the preparation method of the above method 2, the first monomer of the polyamide solution is 4,4-diaminodiphenyl ether, the second monomer is pyrophthalic anhydride, the molar ratio of 4,4-diaminodiphenyl ether to pyrophthalic anhydride is 1:1, the concentration of the polyamide solution is 0.5 mol / L, the drying insulation temperature is 25°C, the insulation time is 2h, the reaction temperature of the imidization reaction is 300°C, the reaction time is 2h, and the ambient atmosphere is argon atmosphere.

[0072] Figure 2 is a scanning electron microscope image of the untreated carbon fiber in Example 1 of the present invention, Figure 3 is a scanning electron microscope image of the pretreated carbon fiber in Example 1 of the present invention, Figure 4 is a scanning electron microscope image of the carbon fiber coated with only a zirconium oxide layer prepared in Example 1 of the present invention, Figure 5 This is a scanning electron microscope image of the carbon fiber coated with a zirconium oxide layer and a polyimide layer prepared in Example 1 of the present invention. It can be seen from the image that the surface of the untreated carbon fiber is relatively flat, and many grooves appear on the surface of the carbon fiber after pretreatment, which increases the specific surface area of ​​the material; Figure 6 is a scanning electron microscope image of the composite carbon fiber prepared in Example 1 of the present invention, Figure 7This is a scanning electron microscope image of the composite carbon fiber prepared in Example 1 of the present invention after ablation. It can be seen from the figure that after the carbon fiber is coated with the zirconium oxide layer and the polyimide layer, the thickness of the composite carbon fiber material is significantly increased, and there is a coating layer on the surface of the unablated cross-section reinforced composite carbon fiber material, and no large pores appear at the interface after ablation, and the interface strength is high.

[0073] Example 2

[0074] The present embodiment provides a composite carbon fiber, which includes T700 carbon fiber, a zirconium oxide layer coated on the surface of the T700 carbon fiber, and a polyimide layer coated on the surface of the zirconium oxide layer, wherein the coating thickness of the zirconium oxide is 0.1 μm, and the coating thickness of the polyimide is 0.2 μm.

[0075] The preparation method of the composite carbon fiber provided in this embodiment comprises the following steps:

[0076] (1) The T700 carbon fiber is sequentially cleaned with ethanol, subjected to reflux treatment for degumming, and subjected to acid immersion, and then washed with deionized water until the pH of the washing solution is 7, thereby obtaining a pretreated carbon fiber; the reflux treatment medium includes acetone, the acid immersion solvent includes nitric acid with a mass concentration of 30%, and the acid immersion time is 12 hours;

[0077] (2) After the carbon fiber is first impregnated in zirconium oxychloride sol, a gelation reaction is performed to obtain a carbon fiber coated with a zirconium oxide layer; the concentration of the zirconium oxychloride sol is 0.01 mol / L, the insulation temperature of the first impregnation is 70° C., the insulation time is 1 h, the reaction temperature of the gelation reaction is 800° C., the reaction time is 0.5 h, and the ambient atmosphere is a nitrogen atmosphere;

[0078] (3) After the zirconium oxide layer-coated carbon fiber is immersed in a polyamide solution for a second time, drying and imidization reaction are carried out in sequence to obtain the composite carbon fiber; the polyamide solution is prepared by the preparation method of the above method 1, the monomer of the polyamide solution is 4,4-diaminodiphenyl ether, the concentration of the polyamide solution is 0.01 mol / L, the drying insulation temperature is 30°C, the insulation time is 1h, the reaction temperature of the imidization reaction is 400°C, the reaction time is 0.5h, and the ambient atmosphere is a nitrogen atmosphere.

[0079] Example 3

[0080] The present embodiment provides a composite carbon fiber, which includes T800 carbon fiber, a zirconium oxide layer coated on the surface of the T800 carbon fiber, and a polyimide layer coated on the surface of the zirconium oxide layer, wherein the coating thickness of the zirconium oxide is 2 μm, and the coating thickness of the polyimide is 5 μm.

[0081] The preparation method of the composite carbon fiber provided in this embodiment comprises the following steps:

[0082] (1) washing the T800 carbon fiber with isopropanol, performing reflux treatment to remove the glue and acid leaching, and then washing with deionized water until the pH of the washing liquid is 7, to obtain a pretreated carbon fiber; the reflux treatment medium includes acetone, the acid leaching solvent includes nitric acid with a mass concentration of 50%, and the acid leaching time is 4 hours;

[0083] (2) After the carbon fiber is first impregnated in zirconium oxychloride sol, a gelation reaction is performed to obtain a carbon fiber coated with a zirconium oxide layer; the concentration of the zirconium oxychloride sol is 2 mol / L, the insulation temperature of the first impregnation is 50° C., the insulation time is 3 h, the reaction temperature of the gelation reaction is 200° C., the reaction time is 24 h, and the ambient atmosphere is an argon atmosphere;

[0084] (3) The zirconium oxide layer-coated carbon fiber is immersed in a polyamide solution for a second time, and then dried and imidized to obtain the composite carbon fiber; the polyamide solution is prepared by the preparation method of the above method 1, the monomer of the polyamide solution is 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene, the concentration of the polyamide solution is 1 mol / L, the drying insulation temperature is 20°C, the insulation time is 3h, the reaction temperature of the imidization reaction is 200°C, the reaction time is 6h, and the ambient atmosphere is argon atmosphere.

[0085] Example 4

[0086] The only difference between this embodiment and embodiment 1 is that, except that the concentration of the zirconium oxychloride sol in step (2) is 0.005 mol / L, the rest is the same as embodiment 1.

[0087] Example 5

[0088] The only difference between this embodiment and embodiment 1 is that, except that the concentration of the zirconium oxychloride sol in step (2) is 2.1 mol / L, the rest is the same as embodiment 1.

[0089] Example 6

[0090] The only difference between this embodiment and embodiment 1 is that, except that the reaction temperature of the gelation reaction in step (2) is 150° C., the rest is the same as embodiment 1.

[0091] Example 7

[0092] The only difference between this embodiment and embodiment 1 is that, except that the reaction temperature of the gelation reaction in step (2) is 850° C., the rest is the same as embodiment 1.

[0093] Example 8

[0094] The only difference between this embodiment and embodiment 1 is that, except that the concentration of the polyamino acid solution in step (3) is 0.005 mol / L, the rest is the same as embodiment 1.

[0095] Example 9

[0096] The only difference between this embodiment and embodiment 1 is that, except that the concentration of the polyamino acid solution in step (3) is 1.1 mol / L, the rest is the same as embodiment 1.

[0097] Example 10

[0098] The only difference between this embodiment and embodiment 1 is that, except that the reaction temperature of the imidization reaction in step (3) is 150° C., the rest is the same as embodiment 1.

[0099] Embodiment 11

[0100] The only difference between this embodiment and embodiment 1 is that, except that the reaction temperature of the imidization reaction in step (3) is 450° C., the rest is the same as embodiment 1.

[0101] Example 12

[0102] The difference between this embodiment and embodiment 1 is that, except that the pretreatment in step (1) is not performed, the rest is the same as embodiment 1.

[0103] Example 13

[0104] The difference between this embodiment and embodiment 1 is that, except that acid leaching is not performed in step (1), the rest is the same as embodiment 1.

[0105] Comparative Example 1

[0106] The difference between this comparative example and Example 1 is that, except that step (2) and step (3) are not performed and only pretreated carbon fiber is obtained, the rest is the same as Example 1.

[0107] Figure 8 This is a scanning electron microscope image of the composite carbon fiber prepared in comparative example 1 of the present invention after ablation. It can be seen from the image that only the surface of the pretreated carbon fiber is obviously cracked after ablation, and larger pores appear, and the interface strength is low.

[0108] Comparative Example 2

[0109] The difference between this comparative example and Example 1 is that, except that step (3) is not performed and only the pretreated carbon fiber coated with zirconium oxide layer is obtained, the rest is the same as Example 1.

[0110] Comparative Example 3

[0111] The difference between this comparative example and Example 1 is that, except that step (2) is not performed and only the pretreated carbon fiber-coated polyimide layer is obtained, the rest is the same as Example 1.

[0112] Test Method

[0113] (1) Morphology test: A scanning electron microscope (JSM-7001F) was used to perform SEM tests on the untreated carbon fiber in Example 1, the pretreated carbon fiber, the carbon fiber coated with only a zirconium oxide layer, the carbon fiber coated with a zirconium oxide layer and a polyimide layer, the composite carbon fiber obtained in Example 1, and the product obtained after ablation of the composite carbon fiber obtained in Example 1 and Comparative Example 1 to obtain corresponding scanning electron microscope images.

[0114] (2) Ablation resistance: The ablation resistance of the composite carbon fibers prepared in Examples 1 to 13 and Comparative Examples 1 to 3 was tested using an oxyacetylene flame combustion platform. The ablation platform parameters are shown in Table 1, and the test results are recorded in Table 2.

[0115] (3) Interface shear strength (IFSS): The interface shear strength test was conducted using the Model HM410 composite material interface performance evaluation device produced by Toei Industry Co., Ltd. of Japan. Resin microspheres with an embedding length of 100 μm were selected on the composite carbon fibers described in Examples 1 to 13 and Comparative Examples 1 to 3, and a cutter head was fixed on one side of the microspheres. The cured resin microspheres were debonded from the carbon fiber monofilaments at a fixed speed of 0.12 mm / min. The sensor received the load F and the test results were recorded in Table 2. Interface shear strength meter

[0116] IFSS= F max

[0117] The calculation formula is: πdl, where F max is the maximum instantaneous load received by the sensor, d is the diameter of the carbon fiber, and l is the length of the resin microsphere and the carbon fiber.

[0118] Table 1

[0119] Combustion gas Acetylene Oxygen acetylene mixture ratio 1.35 Nozzle diameter 2.0mm Gas working pressure 0.095MPa Ablation distance 10mm Gas flow rate <![CDATA[1.116m 3 / h]]> Ablation Angle 90° Heat flux <![CDATA[4186.8kW / m 2 ±10%]]> Temperature measurement High temperature infrared Ablation time 20s

[0120] Table 2

[0121]

[0122]

[0123] The test results show that:

[0124] (1) It can be seen from Examples 1 to 13 and Comparative Examples 1 to 3 that in the composite carbon fiber material of the present invention, the zirconium oxide layer can improve its heat resistance and ablation resistance, and the polyimide layer can enhance its interface shear resistance. The two work together to prepare a composite carbon fiber material with excellent mechanical properties and heat resistance and ablation resistance. The present invention prepares a multilayer interface of carbon fiber-zirconium oxide-polyimide from inorganic to organic, constructs a modulus and heat resistance gradient from carbon fiber to polyimide resin, and improves the interface performance of the composite carbon fiber material. Zirconium oxide will partially enter the polyimide layer, improve the interface fusion between zirconium oxide and polyimide, and help improve the comprehensive performance of the composite carbon fiber material.

[0125] (2) It can be seen from Examples 1 and 4 to 7 that the present invention can further reduce the mass ablation rate of the composite carbon fiber material and improve the heat resistance and ablation resistance of the composite carbon fiber material by further regulating the concentration of the zirconium oxychloride sol and the reaction temperature of the gelation reaction, while further improving the interface shear strength and improving the interface shear resistance of the composite carbon fiber material.

[0126] (3) It can be seen from Example 1 and Example 8 to Example 11 that the present invention can further reduce the mass ablation rate of the composite carbon fiber material and improve the heat resistance and ablation resistance of the composite carbon fiber material by further regulating the concentration of the polyamide solution and the reaction temperature of the imidization reaction, while further improving the interface shear strength and improving the interface shear resistance of the composite carbon fiber material.

[0127] (4) It can be seen from Example 1 and Example 12-Example 13 that the present invention can further reduce the mass ablation rate of the composite carbon fiber material and improve the heat resistance and ablation resistance of the composite carbon fiber material by further pretreating the carbon fiber and further limiting the pretreatment to include a pickling step, while further improving the interface shear strength and improving the interface shear resistance of the composite carbon fiber material.

[0128] In summary, in the composite carbon fiber material of the present invention, the zirconium oxide layer can improve its heat resistance and ablation resistance, and the polyimide layer can enhance its interface shear resistance. The two work together to prepare the composite carbon fiber material with excellent mechanical properties and heat resistance and ablation resistance. The present invention prepares a multilayer interface of carbon fiber-zirconium oxide-polyimide from inorganic to organic, constructs a modulus and temperature resistance gradient from carbon fiber to polyimide resin, and improves the interface performance of the composite carbon fiber material. Zirconium oxide will partially enter the polyimide layer, improve the interface fusion between zirconium oxide and polyimide, and help improve the comprehensive performance of the composite carbon fiber material.

[0129] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite carbon fiber, characterized in that: The composite carbon fiber comprises carbon fiber, a zirconium oxide layer coated on the surface of the carbon fiber, and a polyimide layer coated on the surface of the zirconium oxide layer.

2. The composite carbon fiber according to claim 1, characterized in that The carbon fiber includes any one of T300 carbon fiber, T700 carbon fiber, T800 carbon fiber or T1000 carbon fiber, or a combination of at least two of them.

3. The composite carbon fiber according to claim 1 or 2, characterized in that: The thickness of the zirconium oxide layer is 0.1 μm-2 μm; Preferably, the thickness of the polyimide layer is 0.2 μm-5 μm.

4. A method for preparing a composite carbon fiber according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The carbon fiber is first immersed in zirconium oxychloride sol, and then a gelation reaction is performed to obtain carbon fiber coated with a zirconium oxide layer; the carbon fiber coated with a zirconium oxide layer is second immersed in a polyamide solution, and then an imidization reaction is performed to obtain the composite carbon fiber.

5. The preparation method according to claim 4, characterized in that: The carbon fiber is pretreated before the first impregnation; Preferably, the pretreatment comprises cleaning, degumming and pickling performed in sequence; Preferably, the cleaning agent comprises ethanol and / or isopropanol; Preferably, the degumming method includes a reflow treatment; Preferably, the immersion time of the acid leaching is 4h-12h.

6. The preparation method according to claim 4 or 5, characterized in that: The concentration of the zirconium oxychloride sol is 0.01 mol / L-2 mol / L.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The reaction temperature of the gelation reaction is 200°C-800°C; Preferably, the reaction time of the gelation reaction is 0.5h-24h.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The monomers of the polyamidoamine solution include any one or a combination of at least two of 4,4-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)-2-tert-butylbenzene, pyromellitic anhydride or 3,3,4,4-biphenyltetracarboxylic dianhydride; Preferably, the concentration of the polyamino acid solution is 0.01 mol / L-1 mol / L.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The reaction temperature of the imidization reaction is 200°C-400°C; Preferably, the reaction time of the imidization reaction is 0.5h-6h.

10. An application of the composite carbon fiber according to any one of claims 1 to 3, characterized in that: The composite carbon fiber is applied to aerospace structural materials.

Citation Information

Patent Citations

  • Preparation method of ultrahigh-temperature silicon carbide ceramic-based composite material and ultrahigh-temperature silicon carbide ceramic-based composite material

    CN114163252A

  • Preparation method of anti-oxidation ablation coating on surface of C / C composite material

    CN115028472A

  • Cf / Ta4HfC5-SiC ultrahigh-temperature-resistant composite material and preparation method thereof

    CN115286407A

  • Preparation method of carbon fiber enhanced polyimide based composite material

    CN109265998A

  • Carbon fiber / zirconium oxide composite material as well as preparation method and application thereof

    CN114687203A